Antepartum risk factors for newborn encephalopathy: the Western Australian case-control study - Badawi, Nadia (British Medical Journal, 1998)
OBJECTIVE: To ascertain antepartum predictors of newborn encephalopathy in term infants. DESIGN: Population based, unmatched case-control study. SETTING: Metropolitan area of Western Australia, June 1993 to September 1995. SUBJECTS: All 164 term infants with moderate or severe newborn encephalopathy; 400 randomly selected controls. MAIN OUTCOME MEASURES: Adjusted odds ratio estimates. RESULTS: The birth prevalence of moderate or severe newborn encephalopathy was 3.8/1000 term live births. The neonatal fatality was 9.1%. The risk of newborn encephalopathy increased with increasing maternal age and decreased with increasing parity. There was an increased risk associated with having a mother who was unemployed (odds ratio 3.60), an unskilled manual worker (3.84), or a housewife (2.48). Other risk factors from before conception were not having private health insurance (3.46), a family history of seizures (2.55), a family history of neurological disease (2.73), and infertility treatment (4.43). Risk factors during pregnancy were maternal thyroid disease (9.7), severe pre-eclampsia (6.30), moderate or severe bleeding (3.57), a clinically diagnosed viral illness (2.97), not having drunk alcohol (2.91); and placenta described at delivery as abnormal (2.07). Factors related to the baby were birth weight adjusted for gestational age between the third and ninth centile (4.37) or below the third centile (38.23). The risk relation with gestational age was J shaped with 38 and 39 weeks having the lowest risk. CONCLUSIONS: The causes of newborn encephalopathy are heterogeneous and many of the causal pathways start before birth.